The structure of denitrifying microbial communities in constructed mangrove wetlands in response to fluctuating salinities. (15th May 2019) - Fu, Guiping; Han, Jingyi; Yu, Tianyu; Huangshen, Linkun; Zhao, Lin
Abstract: In this study, the experimental vertical-flow constructed wetland (CW) systems planted with the salt-tolerant mangrove species Kandelia candel were established to investigate the influence of salinity fluctuations on the denitrification performance and denitrifying microbial community structure of the CWs. The high-throughput sequencing analysis showed that 10–13 genera aerobic microbes had been enriched in the upper layer of wetland matrix in the depth of 10–25 cm, with the relative abundance accounting for 19.1 ± 7.9%. Although the ammonium oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB) were inhibited significantly in the CW systems with salinity levels in the range of 0.9–1.8%, the aerobic denitrifying (AD) bacteria including Pseudomonas, Acinetobacter and Aeromonas, removed 99% of ammonia nitrogen from the influent by heterotrophic nitrification (HN) functions, and conducted denitrification at the same time to remove 90% of the TN in the system, indicating that the wetland test system successfully enriched a variety of aerobic denitrifying bacterial communities under different salinity conditions. Not only the nitrogen removal efficiency but also the adaptability of the wetland system to salinity fluctuations had been improved by the enriched HN-AD bacteria. In addition, HN-AD bacterial communities can conduct both nitrification and denitrification in the middle and upper layers of the vertical flow wetland, hereby saving the reaction space of the constructed wetland and reducing the construction cost. Highlights: AD bacterial communities were enriched in the 10–25 cm layers of K. candel CW. HN-AD bacteria performed nitrification when high salinity inhibited AOB. AD bacteria enabled denitrification to occur in the upper layer of the CW. Enriched Zobellella resulted in 90% TN removal rate at 0.9–1.8% salinity.